The Impact of Maternal Oral Health Knowledge and Behavior on Children’s Oral Health Status: A Cross-Sectional Study - Razeghi, Samaneh; Mohammadalizadeh, Maryam; Khami , Mohammad Reza; Kashefi baher, Mohammadreza; Yeganehfard , Hodays; Hasani , Mahsa; Kharazifard, Mohammad Javad (Journal of Dental School, 2025)
Objective(s): The extent to which mothers’ oral health, knowledge, and attitudes influence their children’s oral health remains a subject of debate. Many researchers consider parents’ inadequate knowledge and attitudes regarding their children’s oral health to be responsible for poor oral health outcomes. This study investigated the level of knowledge regarding the prevention of dental caries and its impact on oral health-related behaviors among mothers. Methods: In this cross-sectional study, 196 mother-child pairs were selected, with children aged 5 to 12 years seeking dental treatment. A questionnaire was provided to the mothers, including demographic information, the mothers’ oral health behaviors, the children’s oral health behaviors, and the mothers’ knowledge of methods for preventing dental caries. In addition, an oral health examination was conducted to measure the child’s DMFT/dmft index. Quantitative variables were described using central tendency and distribution measures, while qualitative variables were reported using frequency percentages. T-test/Mann-Whitney were used to compare quantitative variables. For the comparison of qualitative variables, the Chi-square test was applied at p<0.05. Results: There was a significant relationship between the oral health behaviors of mothers and those of their children. Although mothers’ knowledge of caries prevention was moderate, both mothers’ and children’s behaviors were unsatisfactory. No significant relationships were found between the mothers’ knowledge and their oral health behaviors, their children’s oral health behaviors, or the children’s DMFT/dmft scores. Conclusion: Educational interventions should focus on improving mothers’ oral health behaviors to promote oral health in children. Further studies are needed to evaluate the relationship between knowledge and its impact on oral health behaviors.